Compound small peptide of Chinese medicine alleviates cyclophosphamide induced immunosuppression in mice by Th17/Treg and jejunum intestinal flora - Cui, Yuqing; Zhang, Lu; Liu, Ying; Liu, Wei; Shi, Wanyu; Bao, Yongzhan (Frontiers in Microbiology, 2023)
The aim of this study was to explore the efficacy of Compound small peptide of Chinese medicine (CSPCM) on cyclophosphamide (CTX) induced immunosuppression in mice. The 100 male Kunming mice were divided into 5 groups: group A (control group), group B (model group), group C (100 mg/kg.bw CSPCM), group D (200 mg/kg.bw CSPCM) and group E (400 mg/kg.bw CSPCM). At 1–3 days, mice of group B, C, D and E were intraperitoneally injected with 80 mg/kg.bw CTX. The results showed that compared with group A, the immune organ index, body weight change, RORγ T gene expression, RORγ T protein expression, CD3+ cell number, Th17 number and Alpha index, white blood cell count, lymphocyte count and monocyte count were significantly decreased in group B (p < 0.05), while Foxp3 gene expression, Foxp3 protein expression and Treg cell number were significantly increased (p < 0.05), CSPCM has a good therapeutic effect on the above abnormalities caused by CTX. CTX caused the decrease of intestinal flora richness and the abnormal structure of intestinal flora, and CSPCM could change the intestinal flora destroyed by CTX to the direction of intestinal flora of healthy mice. On the whole, CSPCM has a good therapeutic effect on CTX-induced immunosuppression in mice, which is reflected in the index of immune organs, the number of T lymphocytes and Th17 cells increased, the number of Treg cells decreased and the structure of intestinal flora was reconstructed.